ตัวแบบบูรณาการงานป้องกันและแก้ไขการตั้งครรภ์ในวัยรุ่น: ความหมายและการดำเนินงาน - จิรวัฒน์กุล ศิริพร; ฟองแก้ว วารุณี; รุ่งเรืองกลกิจ สมพร (Journal of Thailand Nursing and Midwifery Council, 2017)
Objective: This article presents the fndings of the frst phase of the study conducted as part of the provincial-level research and evaluation project for the prevention of and solution to teenage pregnancy. The main objectives of the study were to defne the meaning of ‘integration’ as perceived by the provincial working group and to identify an integrated operation model. Design: Mixed-method research, concurrent qualitative and descriptive approaches. Methodology: Qualitative data were collected by means of observation, group discussions, in-depth interviews and documentary analysis. The respondents, who were selected using the purposive sampling method combined with word-of-mouth suggestion, their number saturated at 492, were working-group operators from Chiang Rai, Phayao, Chiang Mai, Lamphun, Lampang, Tak, Nakhon Sawan, Nakhon Ratchasima, Chaiyaphum, Loei, Maha Sarakham, Khonkaen, Nakhon Phanom, Chachoengsao, Suphan Buri, Phetcha Buri, Prajuab Khirikhan and Krabi provinces. The qualitative data were analysed using the thematic analysis method. The descriptive research part was based on data obtained through structured interviews with 18 project managers. The data were analysed using the content and thematic analysis methods. Finally, the results of both types of analysis were integratively discussed. Results: The term ‘integration’ was defned as entailing open-mindedness, mutual learning and cooperative efforts, all combined to form a network. The integration models were identifed as involving 4 styles of operation: (1) a meeting for all, before each team was dispersed with a responsibility; (2) plan announcement, before each team was dispersed with a task; (3) brainstorming, collating the tasks, assembling the people and pooling money; and (4) brainstorming and operation. Recommendations: The integration models involving the ‘brainstorming, collating the tasks, assembling the people and pooling money’ and the ‘brainstorming and operation’ styles were implemented in a horizontal, rather than vertical, manner. These 2 styles, therefore, enabled the staff from all sectors to learn from one another, to work together pleasantly and to likely produce the intended results. It is suggested that nurses be trained to apply these integration models as a means of enhancing their community- and clinical-level disease prevention and health promotion performance.